Shear strain influence in the service response of FRP reinforced concrete beams. (March 2015) - Ferreira, Denise; Oller, Eva; Barris, Cristina; Torres, Lluis
Abstract: Shear strains can become significant in the response of RC beams, especially in the case with longitudinal FRP reinforcement. The effect of the shear strains is studied in this paper through the numerical results of a 1D non-linear fibre model accounting for the axial–bending–shear interaction. Experimental data from FRP RC beams, tested by the authors, are compared with the numerical results determined with the shear-sensitive and with a pure flexural 1D model in order to evaluate the effect of shear. A good correlation in terms of ultimate loads, deflections, strains in the concrete and reinforcement was observed between the experimental and numerical results when considering the shear strains, which represent around 15% of the deflections. The load–deflection response has also been compared with the analytical values given by the JSCE guidelines, showing a good agreement. The numerical model is also able to reproduce the cracking widths and pattern when increasing the applied load. Finally, a parametric study has been performed to analyse the effects of different parameters, such as the longitudinal and transverse reinforcement ratio, the modulus of elasticity of the longitudinal reinforcement, and the shear-span to depth ratio, on the shear deflections.